STUDI ANALISIS PENDIDIKAN ANAK DALAM PANDANGAN ISLAM PENDIDKAN ANAK DALAM ISLAM PERSPEKTIF ABDULLAH NASIH ULWAN DALAM KITAB TARBIYATUL AULAD FILL ISLAM - Zaidul Hudri; Ahmad Khumaidi; Taufiqurohman (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2024)
The weakening of children's education that occurs in Indonesia as well as the problems experienced by national education and Islamic educators as well as the increase in delinquency committed by children. identifying the need to improve children's education, education that is not only focused on intellectual intelligence but education that reaches the areas of morals and personality according to religious teachings. This research aims to explain the methods and material presented by Abdullah Nasih Ulwan. This type of library research uses a qualitative approach. The data collection technique is document and content analysis as an analysis technique. There are several findings from this research, namely Abdullah Nasih Ulwan believes that children's education in Islam pays more attention to children's morals and aqidah. According to Ulwan, there are several materials, namely: faith, morals, intellectual, physical, psychological and social education. He believes that educational methods include: the example method, the habituation method, the advice method, the attention method, and the punishment method